Critical Analysis and Performance Optimization of Waste Management Facilities in Pontianak City - Nur, Maulana; Nur, Syafrial; Nawawi, Nawawi (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2025)
The rapid population and economic growth in Pontianak City have significantly increased waste generation, yet the capacity of existing waste management infrastructure remains insufficient. This study evaluates the facility requirements necessary for achieving the national waste reduction target of 30% by 2025, as stipulated in Presidential Decree No. 97 of 2017. Utilizing secondary data from SIPSN, the Environmental and Forestry Office, and the Central Statistics Agency, a simple linear regression model was employed to project waste generation from 2023–2025 using SPSS version 22. The results indicate a strong correlation between population growth and waste generation (R² = 0.914), with projected waste reaching 134,606 tons by 2025. A 30% reduction would require the diversion of 40,381 tons. Simulation analysis highlights the need for expanding TPS3R and Waste Bank Units, as well as optimizing current facility capacity. This study recommends strategic investment in infrastructure and operational fleets to meet the 2025 waste reduction target.